2021
DOI: 10.1371/journal.pone.0257575
|View full text |Cite|
|
Sign up to set email alerts
|

Anthropogenic factors are stronger drivers of patterns of endemic plant diversity on Hainan Island of China than natural environmental factors

Abstract: The roles of natural and anthropogenic factors in contributing to the organization of biodiversity at large and small scales have long been challenging to disentangle, and doing so has never been attempted for the island province of Hainan in China based on patterns of taxonomic and phylogenetic diversity. Therefore, in this study, we evaluated the taxonomic and phylogenetic diversity of endemic plants on the island as a function of anthropogenic and natural variables based on non-metric multi-dimensional scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In fact, the environments of continents and islands at the same latitude are quite different, as is the forest soil. Nonmetric multidimensional scaling (NMDS) and principal-coordinate analysis (PCA) showed that the points on Hainan Island were more discrete than those on the other stations ( 3 5 ); this showed that the island environment different from the mainland affects the soil fungal community ( 10 , 11 ). The soil P content of forests on Hainan Island is higher than that of the continental forests at the same latitude, and C, N, P, and their ratios exhibit large spatial variations on the island ( 12 ).…”
Section: Observationmentioning
confidence: 99%
“…In fact, the environments of continents and islands at the same latitude are quite different, as is the forest soil. Nonmetric multidimensional scaling (NMDS) and principal-coordinate analysis (PCA) showed that the points on Hainan Island were more discrete than those on the other stations ( 3 5 ); this showed that the island environment different from the mainland affects the soil fungal community ( 10 , 11 ). The soil P content of forests on Hainan Island is higher than that of the continental forests at the same latitude, and C, N, P, and their ratios exhibit large spatial variations on the island ( 12 ).…”
Section: Observationmentioning
confidence: 99%
“…For 19 administrative units, we obtained the following environmental varaobles: (1) minimum temperature of the coldest month (BIO6), (2) maximum temperature of the warmest month (BIO5), (3) mean temperature of the warmest quarter (BIO10), (4) mean temperature of the coldest quarter (BIO11), and (5) mean annual precipitation (BIO12). These variables are known to be key to determining land plant distributions (Harris et al, 2017;Cheval et al, 2020;Li et al, 2020;Xie et al, 2021;Zhu et al, 2021). Moreover, due to the well-known relationship between species diversity and area (Arrhenius, 1921;Barkman, 1989;Zhou et al, 2020), we also obtained land area data (km 2 ).…”
Section: Socioeconomic and Natural Environmental Variablesmentioning
confidence: 99%
“…However, working at such a large scale can indicate the relative importance of environmental and anthropogenic factors. One study on stream macro‐invertebrates showed that natural environmental gradients could mask the effect of perturbations on biodiversity (Heino et al, 2007), contrary to what has been found in terrestrial ecosystems (Zhu et al, 2021). Other studies in stream insects showed that anthropogenic disturbances could modify the relationship between environmental factors and diversity (Agra et al, 2021).…”
Section: Introductionmentioning
confidence: 98%